First report of reddish brown spot disease of red-fleshed dragon fruit (Hylocereus polyrhizus) caused by Nigrospora lacticolonia and Nigrospora sphaerica in Malaysia. (August 2019) - Kee, Y.J.; Hafifi, A.B.M.; Huda-Shakirah, A.R.; Wong, K.L.; Jin, X.L.; Siti Nordahliawate, M.S.; Zakaria, L.; Mohd, M.H.
Abstract: Stems of red-fleshed dragon fruit (Hylocereus polyrhizus) with reddish brown spots were collected from Negeri Sembilan and Johor in Malaysia. Based on morphological and molecular characteristics, the fungi isolated from the stems were identified as Nigrospora lacticolonia and N. sphaerica . Phylogenetic analysis of internal transcribed spacer (ITS) region, β-tubulin and translation elongation factor 1-α (TEF1-α) genes confirmed the species identification. The fungal isolates produced reddish brown spot on the inoculated stems. This is the first report of N. lacticolonia and N. sphaerica as the pathogens of dragon fruit plant in Malaysia. Highlights: Reddish brown spot disease on dragon fruit was firstly reported in Malaysia. Nigrospora lacticolonia and N. sphaerica were causal pathogens of the disease. Identity of the pathogens was confirmed through morphology and DNA sequences. The size of conidia of N. sphaerica was relatively bigger than N. lacticolonia. Both Nigrospora were phylogenetically different based on ITS, β-tubulin and TEF1-α.